Teachers’ perceptions of lessons using computer assisted language learning - Mohd. Nor , Faizah; Malar Vasu, Sumitha (2010)
The present study was designed to investigate the teachers’ perceptions of CALL lessons. The objectives of this study are to find out the problems faced by the teachers when conducting CALL lessons, to identify the perceptions teachers have on such lessons and also to investigate teachers’ perceptions of the effectiveness of the lessons using CALL on students. Questionnaires were distributed to 16 teachers who are currently teaching English at secondary schools in Johor Bahru. The data collected were analyzed using qualitative data. The problems identified in using CALL lessons were problems with facilities and problems with teachers’ attitudes. However, teachers had positive perceptions of CALL lessons as it helps teachers to attract students’ attention in the classroom and CALL lessons promote enhanced language acquisition.